2015
DOI: 10.1136/bjophthalmol-2015-307050
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associations of epiretinal membrane in an elderly urban Chinese population in China: the Jiangning Eye Study

Abstract: The prevalence of ERM in elderly urban Chinese was similar to that in Caucasians. Risk factors for idiopathic ERM were older age, female gender, myopia and hyperlipaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 22 publications
7
37
1
Order By: Relevance
“…This intraethnic variation was not fully explained by age or other potential confounders. In keeping with our finding, the Multi-Ethnic Study of Atherosclerosis also demonstrated that ERM prevalence was highest among Chinesecompared with other non-Asian populations 4 16. However, other studies in Chinese have reported lower prevalence rates than that of our study,17 although differences in participant characteristics and methodology in ERM assessment preclude direct comparison with our results.…”
Section: Discussionsupporting
confidence: 82%
“…This intraethnic variation was not fully explained by age or other potential confounders. In keeping with our finding, the Multi-Ethnic Study of Atherosclerosis also demonstrated that ERM prevalence was highest among Chinesecompared with other non-Asian populations 4 16. However, other studies in Chinese have reported lower prevalence rates than that of our study,17 although differences in participant characteristics and methodology in ERM assessment preclude direct comparison with our results.…”
Section: Discussionsupporting
confidence: 82%
“…In further evaluation of the remaining 18 articles, 10 were excluded for the following reasons: 6131435363738 did not report the risk factor of smoking; 351139 could not provide essential data after contacting the corresponding authors and 115 did not meet the definition of smoking. In the end, two cohort studies1018 and six cross-sectional studies91216174041 met our criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence rate of iERM in those aged 50 or older was recently estimated to be 7.7%, which is higher than that of early age-related macular degeneration (6.8%)23. The development of iERM basically requires the remnant of posterior vitreous cortex on the surface of the posterior retina as well as the migration and proliferation of Müller glial cells, both of which are triggered by posterior vitreous detachment4567.…”
mentioning
confidence: 99%